2010
DOI: 10.3945/ajcn.2009.28401
|View full text |Cite|
|
Sign up to set email alerts
|

Folic acid source, usual intake, and folate and vitamin B-12 status in US adults: National Health and Nutrition Examination Survey (NHANES) 2003–2006

Abstract: At current fortification levels, US adults who do not consume supplements or who consume an average of < or =400 microg folic acid/d from supplements are unlikely to exceed the UL in intake for folic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 17 publications
8
123
0
1
Order By: Relevance
“…Third, Japanese dietary folate intake may be more difficult to estimate than intake in other countries (40). This is probably because folate is derived mainly from fortified foods or supplements in other countries (24,26) and the variety of folate sources in such countries may be relatively limited compared to the variety in Japan. Fourth, the number of subjects with the TT genotype and higher plasma tHcy levels in our study was relatively small to examine the associations in such groups.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Third, Japanese dietary folate intake may be more difficult to estimate than intake in other countries (40). This is probably because folate is derived mainly from fortified foods or supplements in other countries (24,26) and the variety of folate sources in such countries may be relatively limited compared to the variety in Japan. Fourth, the number of subjects with the TT genotype and higher plasma tHcy levels in our study was relatively small to examine the associations in such groups.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, the mean and standard deviation (SD) of folate intake was 772611 mg dietary folate equivalents (DFE)/d, including only 19962 mg DFE/d from natural sources among the American population from 2003 to 2006 (24). In several countries including the United States, fortified foods or folic acid supplements are important sources of folate (24)(25)(26), and supplemented folate is more ther-mostable than folate from natural foods (27). The role of the MTHFR polymorphism in folate metabolism may be different in areas where folate intake is relatively low.…”
mentioning
confidence: 99%
“…In 2010, an expert roundtable advised CDC on folate biomarkers and methods for future NHANES surveys [1]. Because in the era of post-fortification, public health concerns are no longer limited to low folic acid intakes, but extend to the safety of high intakes, which are largely driven by supplement use [2], the roundtable advised NHANES to use a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method in 2011-2012 [1]. This allows for the measurement of individual folate vitamers, including unmetabolized folic acid (FA), and calculation of tFOL by summation of the individual vitamers.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, such as in Ireland and in the UK, the introduction of mandatory folic acid fortification of bread has been advocated (SACN, 2005) and, despite the rising concerns about potential adverse health effects of high folic acid intake levels (Smith et al, 2008;BBC News, 2009, October 20)(see section 2.3.1), implemented. These concerns were also heard in the United States (CDC, 2010) when a recently published study concluded that 2.7% of the adults exceeded the tolerable upper level (UL) of 1 000 µg folic acid per day (Yang et al, 2010).…”
Section: Folic Acid Food Fortification Programsmentioning
confidence: 99%
“…Building upon their review of the dual effects of folic acid intake, Smith et al (2008, p. 517) authorities develop the right strategies for the population as a whole". However, exceedingly high levels of folic acid seem to be more attributable to folic acid supplementation rather than to fortification (Yang et al, 2010).…”
Section: Micronutrient Malnutritionmentioning
confidence: 99%